Ischaemic stroke as initial presentation of systemic malignancy. (3rd March 2014) - Goedee, Stephan; Naber, Alike; Rovers, Jörgen M P; Roks, Gerwin
Abstract : Ischaemic stroke as the initial presentation of systemic malignancy is reported infrequently and is characterised by ischaemic lesions that exceed the vascular territory of a single vessel. There is also a high rate of early stroke recurrence. Several pathophysiological mechanisms are known to cause cerebrovascular complications in malignancies, as a direct effect of the tumour, paraneoplastic or even of the tumour treatment itself. Prognosis is reportedly poor, treatment is symptomatic and at best anecdotal. We present a case report and available literature.